Emergency Relief System Design Using DIERS Technology: The Design Institute for Emergency Relief Systems (DIERS) Project Manual - Fisher, H. G; Forrest, H. S; Grossel, Stanley S; Huff, J. E; Muller, A. R; Noronha, J. A; Shaw, D. A; Tilley, B. J (Wiley, 2010)
OSHA (29 CFR 1910.119) has recognized AIChE/DIERS two-phase flow publications as examples of "good engineering practice" for process safety management of highly hazardous materials. The prediction of when two-phase flow venting will occur, and the applicability of various sizing methods for two-phase vapor-liquid flashing flow, is of particular interest when designing emergency relief systems to handle runaway reactions. This comprehensive sourcebook brings together a wealth of information on methods that can be used to safely size emergency relief systems for two-phase vapor-liquid flow for flashing or frozen, viscous or nonviscous fluids. Design methodologies are illustrated by selected sample problems. Written by industrial experts in the safety field, this book will be invaluable to those charged with operating, designing, or managing today's and tomorrow's chemical process industry facilities.